Size of canine hepatocellular carcinoma as an adverse prognostic factor for surgery - Vatnikov, Yury; Vilkovysky, Ilya; Kulikov, Evgeny; Popova, Irina; Khairova, Nadia; Gazin, Aleksey; Zharov, Andrey; Lukina, Darya (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: Liver neoplasms are problematic among small domestic animals. The etiological cause of hepatocellular carcinomas in domestic animals is still unknown although it is believed that chronic infections and toxic substances can affect the development of this type of tumor. This study aimed to analyze the clinical and morphological characteristics of canine hepatocellular carcinoma. Materials and methods: In total, 6,958 cancer operations were performed in the clinic. Liver tumors were detected in 123 dogs in vivo and 375 dogs postmortem. All animals with suspected liver neoplasm were assessed, including history, clinical examination, complete blood count, biochemical blood tests, radiographic examination, and ultrasound with a biopsy for performing cytological and histological analyses. Results: Hepatocellular carcinomas have nonspecific clinical manifestations, also a characteristic aspect of other tumors of the hepatobiliary system. The hematological changes have an impact on the prognosis, and biochemical abnormalities reflect the changes in liver activity. The cytological diagnosis of hepatocellular tumors is difficult because of hepatocyte atypia in highly differentiated carcinomas. Finally, a histological examination was performed in all the dogs diagnosed with hepatocellular carcinoma. Conclusion: Hematological changes in dogs with hepatocellular carcinoma affect their prognosis. Biochemical abnormalities of this pathology reflect the changes in liver activity, not indicating a specific pathology. However, an increase in the activity of aspartate aminotransferase, alanine aminotransferase, and alkaline phosphatase is an unfavorable prognostic sign. In this study, five of seven dogs with a tumor size of more than 5.0 cm had a life expectancy of 30, 51, and 91 days, suggesting that the size of the tumor is an adverse prognostic factor. J. Adv. Vet. Anim. Res., 7(1): 127-132, March 2020